Socioeconomic inequalities in COVID-19 vaccination and infection in adults, Catalonia, Spain - Roel, E; Raventós, B; Burn, E; Pistillo, A; Prieto-Alhambra, D; Duarte-Salles, T (Centers for Disease Control and Prevention, 2022)
Evidence on the impact of the COVID-19 vaccine rollout on socioeconomic COVID-19–related inequalities is scarce. We analyzed associations between socioeconomic deprivation index (SDI) and COVID-19 vaccination, infection, and hospitalization before and after vaccine rollout in Catalonia, Spain. We conducted a population-based cohort study during September 2020–June 2021 that comprised 2,297,146 adults >40 years of age. We estimated odds ratio of nonvaccination and hazard ratios (HRs) of infection and hospitalization by SDI quintile relative to the least deprived quintile, Q1. Six months after rollout, vaccination coverage differed by SDI quintile in working-age (40–64 years) persons: 81% for Q1, 71% for Q5. Before rollout, we found a pattern of increased HR of infection and hospitalization with deprivation among working-age and retirement-age (>65 years) persons. After rollout, infection inequalities decreased in both age groups, whereas hospitalization inequalities decreased among retirement-age persons. Our findings suggest that mass vaccination reduced socioeconomic COVID-19–related inequalities.